The Effect Of Brown Sugar Suplement On Heart Rate Recovery In Female Volleyball Athletes - Salma Ramadhania; Agung Wahyudi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the effect of brown sugar suplement on heart rate recovery in Voppick Kebumen women's volleyball athletes. This study uses an experimental method with a two-period crossover design. The research sample amounted to 30 female volleyball athletes who were divided into two groups. This research instrument uses bleep test which aims to increase the athlete's pulse until it reaches a tired state, pulse measurement using palpation techniques and also stopwatches to measure recovery time. The results of this study show that brown sugar solution has a significant influence on  the pulse recovery  of Voppick Kebumen women's volleyball athletes. Based on the results of the hypothesis test, it showed a Sig. value of 0.000 < 0.05 with a t-value of 18.489 and the results of  the effect size calculation, obtained a Cohen's d value of 2.212 which belongs to the large category. The conclusion of this study shows that the administration of brown sugar solution drinks has a significant influence on  pulse recovery in women's volleyball athletes Voppick Kebumen. In addition, brown sugar suplement have been shown to be effective in helping to speed up the recovery of the pulse after physical activity.